KOMPARASI BUDAYA MADRASAH DALAM MENGEMBANGKAN LITERASI AGAMA ISLAM (Studi Kasus Di MTs Al-Maliki Cendekia Pekalongan Dengan MTs Al Mahrusiyah Lirboyo Kediri) - Muhamad Fahmi (PT. Saha Kreasi Indonesia, 2025)
The problem addressed in this study concerns the impact of implementing madrasah culture on students and the madrasah environment as a whole. MTs Al Mahrusiyah focuses on understanding the principles, values, and teachings of Islam, which involves theoretical knowledge of beliefs, worship, and Islamic jurisprudence, as well as their application in daily life. MTs Al-Maliki Cendekia, on the other hand, aims to create a learning atmosphere that supports students’ academic, social, and emotional development. This environment must be safe, inclusive, and stimulating to encourage creativity and positive interaction. In general, the understanding and experience of Islamic teachings are closely linked to an individual’s spiritual and moral aspects, while building a conducive student environment relates more to management and support within a broader educational context. Both institutions strive to become high-quality madrasahs those whose educational processes are able to enhance students’ intellectual, emotional, spiritual, and physical competencies in a comprehensive and simultaneous manner. This research employs a qualitative descriptive method to explain the concepts discussed by the author. Through this approach, the study examines the extent to which the implementation of madrasah culture in Islamic religious learning can produce positive impacts on students and the overall madrasah environment. In terms of spiritual and moral development, the improvement of worship practices is evident as students who participate in routine religious activities such as congregational prayers and Qur’anic recitation are able to deepen their understanding and practice.